INLUENCE OF ALIEN GENETIC MATERIAL ON THE MANIFESTATION OF AGRONOMICALLY IMPORTANT TRAITS OF COMMON WHEAT (T. aestivum L.) - I. N. Leonova (Вавиловский журнал генетики и селекции)
Broadening of the genetic diversity of common wheat with respect to genes for resistance to biotic and abiotic stress factors, yield and grain quality is one of the urgent problems of modern genetics and breeding. Wild wheat relatives with diverse levels of the genome homoeology are regularly used for widening the genetic diversity of common wheat for genes that increase disease and insect resistance. Studies on the search and introduction of genetic factors determining the grain protein content and yield are also important. Although resistance genes have a prolonged protective efect on donor plants against diverse populations of pathogens, the introgression of target loci into the genome of common wheat can result in a signiicant decrease in the eiciency of the genes – up to complete loss of expression. Additionally, alien gene introgression from wild relatives occurs through whole chromosome or chromosome arm substitutions, or long translocated fragments that, together with target loci, may contain genetic material that afects other agronomically important traits. Therefore, when introducing disease resistance genes into elite wheat varieties, it is important to take into account the efects of alien substitutions and translocations on such traits as the growth habit, heading date, yield potential, grain and baking quality. Adverse efects observed with gene introgressions from wild species are commonly associated with foreign chromatin linked with target loci. However, in many cases, such efects can be the result of the genetic background of the cultivar-recipient. This article presents an overview of published data on the efect of alien introgressions on agronomically important traits of common wheat.